KEBIJAKAN PENDIDIKAN DI INDONESIA (STUDI TENTANG UPAYA PELAKSANAAN KURIKULUM 2013 OLEH PEMERINTAH KOTA PEKANBARU) - Ayudya, Rereantina Gempita; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Efforts to implement the curriculum in 2013 by the city of Pekanbaru in this case the city education office pekanbaru not running optimally, the implementation of the curriculum in 2013 in the city of Pekanbaru is not running optimally, then through a variable based on the theory of policy implementation by George Edwards III can be found basic formulation of the research problem how the efforts made by the city government in the implementation of the curriculum pekanbaru 2013 in the city of Pekanbaru.Furthermore, the purpose of this study was to determine the curriculum implementation efforts in 2013 were carried out by the city of Pekanbaru. This study used a qualitative model with descriptive method, which is conducted by interview, documentation, and direct observation regarding the implementation of curriculum activities in 2013 in the city of Pekanbaru. In this research method used is an interactive data analysis (interactive models of analysis) of Miles and Huberman which includes data collection, data reduction, data display, and conclusion. The results of this study indicate that the implementation efforts made by the Government of Pekanbaru City concluded that the implementation of a curriculum efforts in 2013 were carried out by performing less well.Keywords: effort, the implementation of policies, curriculum, 2013, the city of Pekanbaru